Nutritional characterization and determination of phytic acid as an anti-nutritional factor of cowpea beans - De-Paula, Claudia Denise (2018)
In Cordoba, Monteria, Colombia, poverty reaches 67.8% of the population, with a generalized food under consumption in the region, and it is estimated that on average, the daily calorie intake is lower than an 18.7%, so, it is necessary to know the qualitative characteristics and the anti-nutritional factors of regional raw materials. The objective of this study was to nutritionally characterize 43 genotypes of cowpea beans and to quantify the phytic acid of the best cultivars based on the study of organic phosphorus content on the samples, assuming that one molecule of this acid contains six molecules of phosphorus, in relation to the protein content and minerals. The genotypes that were used came from Córdoba’s University Genetic Improvement Program; the investigation was developed between 2012 to 2014. The Criollo Córdoba bean sample, which was used as a control, had the highest value in phytic acid content of (12.267 ± 2.15 mg/g) and the cultivar L042 had the lowest phytic acid content (9.630 ± 1.725 mg/g). ), which indicates an improvement in the bioavailability of minerals. The protein content had a range between 22.05% ± 0.82 to 26.90% ± 1.76, and the lines L047, L042, L026, L029, L019 and L002 showed a higher content. The iron amount varied between 59.54% ± 24 and 77-177.90% ± 122.20, excelling in the cultivars L042, L020, L001, L005, L057 and L047, which exceeded the control sample. The tested genotypes showed significant differences (p≤0.05) in phosphorus content and values ranged from 4.64 ± 0.43 to 5.69% ± 0.38%; no cultivar surpassed the control sample. In zinc content, cultivars showed no significant differences (p≥0.05), and ranged between 43.46% ± 4.75 and 10.81 ± 53.38%. L042 cultivar was the best in nutritional and lower phytic acid content as antinutritional substance required to replace the currently consumed varieties of cowpea beans.